Regulation of Nitrate Reductase during Early Seedling Growth (A Role for Asparagine and Glutamine). - Sivasankar, S. (1995)
Growth systems that either permit (wet system) or prevent (dry system) the hydrolysis of endosperm reserves in maize (Zea mays) seedlings were developed to study the effect of endosperm reserves on the acquisition of external nitrogen. Three-day-old seedlings treated with 5 mM KNO3 for 24 h had higher levels of nitrate reductase (NR) activity and protein in shoot and root tissues in the dry relative to the wet system. This suggests that the induction of NR is sensitive to products of hydrolysis of endosperm reserves. Asparagine (1 mM) or glutamine (1 mM), potential products of that hydrolysis, inhibited the induction of NADH-dependent root NR in the dry system by about 70%. The inhibition of the induction of NR activity in the wet system was only about 35%, suggesting that the enzyme in the wet system was already partially repressed at 3 d. At 5 d, when asparagine and glutamine levels in the plant tissue had decreased, the induction of root NR activity was inhibited to a similar extent in the two growth systems by amide additions. The shoot enzyme was less sensitive to amide additions, and 10 mM concentrations of either amide was required for a 65% inhibition.